Obtaining and physicochemical characterization of prebiotic petit suisse of buffalo (Research, Society and Development, 2021)
The objective of this research was the elaboration and physicochemical characterization of petit suisse cheese from buffalo milk fermented with kefir, using inulin as a prebiotic substance in concentrations of 5% (F1), 10% (F2) and 15 % (F3). Initially, the quark cheese mass was obtained by fermenting buffalo milk by kefir, after being drained and washed, the mass was processed with the other ingredients until completely homogenized. The physicochemical characterization was carried out by determining the moisture content, total solids, ash, total acidity titratable in lactic acid, pH, reducing, non-reducing and total sugars, and lipids. The data were subjected to analysis of variance and the comparison of averages was performed by the Tukey test at 5% probability. It was found that the introduction of different concentrations of inulin in the cheese formulation did not influence the ash content, titratable acidity, pH and lipids, but altered the moisture content, total solids and sugars. According to the results in general, it is concluded that formulation 1, with 5% inulin, is the most suitable for the processing of buffalo milk prebiotic petit suisse cheese, due to the use of less prebiotic raw material between samples, which directly influences the cost of the final product and still maintains the functionality of a prebiotic food in accordance with current legislation.